2008
DOI: 10.1002/rra.1173
|View full text |Cite
|
Sign up to set email alerts
|

Construction constraints for geomorphic‐unit rehabilitation on regulated gravel‐bed rivers

Abstract: The emergent practice of applied river restoration uses best available equipment and contouring methods to construct detailed designs with some features at scales as small as 0.5-m relief. As part of adaptive management, it is necessary to determine the practicability of design features and construction methods before widespread adoption. In this study, we compared design versus as-built topography for five salmonid spawning habitat rehabilitation projects at riffle-pool geomorphic units on the lower Mokelumne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, it's been 562 demonstrated that sinusoids approximate many channel features, including bed profiles, 563 as a form of minimum variance (Hallet, 1990. Further, consideringthat there can be inherent error in implementing river restoration designs with heavy 565 equipment (Sawyer et al, 2009), this is not considered a problem as sub channel width 566 scale variations can occur through operator error and variations in bed and bank 567 materials. There has been no research on suitable analytical functions for riffle-pool bed 568 topography, or channel width for that matter, and future research may identify better 569 functions.…”
Section: Using Gcss For Process Based River Design 530mentioning
confidence: 99%
“…However, it's been 562 demonstrated that sinusoids approximate many channel features, including bed profiles, 563 as a form of minimum variance (Hallet, 1990. Further, consideringthat there can be inherent error in implementing river restoration designs with heavy 565 equipment (Sawyer et al, 2009), this is not considered a problem as sub channel width 566 scale variations can occur through operator error and variations in bed and bank 567 materials. There has been no research on suitable analytical functions for riffle-pool bed 568 topography, or channel width for that matter, and future research may identify better 569 functions.…”
Section: Using Gcss For Process Based River Design 530mentioning
confidence: 99%
“…In terrestrial experiments, connectivity is altered by creating or eliminating dispersal corridors, and patch structure is altered by subdividing, removing, enlarging and fusing patches (McGarigal & Cushman, 2002). In temporary rivers, connectivity can be altered by artificially connecting or disconnecting pools, and aquatic and terrestrial patches can be manipulated through sediment excavation and deposition (Sawyer et al. , 2009).…”
Section: Three Emerging Concepts In Temporary River Ecologymentioning
confidence: 99%
“…Restoration of habitat mosaics in degraded temporary-river channels may require excavation and construction of geomorphic structures (e.g. pools, bars, islands), sediment augmentation, and⁄or the provision of large floods (Kondolf & Wilcock, 1996;Sawyer et al, 2009). These geomorphic structures interact with shifting water levels to produce shifting aquatic-terrestrial habitat mosaics.…”
Section: Unique Management Needs For Temporary Riversmentioning
confidence: 99%
“…Based on observed deficiencies of past projects, there is a growing recognition of the importance of design and implementation of complex alluvial features that utilize channel non-uniformity to promote habitat heterogeneity Wheaton et al, 2004b,c;Elkins et al, 2007;Sawyer et al, 2008). There is also a growing need for accurate and cost-effective means to represent habitat (Maddock, 1999;Moir and Pasternack, 2008).…”
Section: Introductionmentioning
confidence: 96%